2009
DOI: 10.1017/s1041610209990184
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of SSRIs on cognition of Alzheimer's disease patients treated with cholinesterase inhibitors

Abstract: In AD patients treated with AChEIs, SSRIs may exert some degree of protection against the negative effects of depression on cognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 26 publications
0
38
0
Order By: Relevance
“…Moreover, rats treated with the TCA amitriptyline from middle to old age had their water maze performance preserved compared with aged controls (Yau et al 2002). In depressed patients affected by AD and treated with AChEIs, Rozzini et al (2010) found that SSRIs might exert some degree of protection against the negative effects of depression on cognition. The present findings also demonstrated that treatment with donepezil resulted in a decrease of latency time in Morris water maze, thereby suggesting that the AlCl 3 -induced spatial learning deficits are related to cholinergic system impairment by the metal.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, rats treated with the TCA amitriptyline from middle to old age had their water maze performance preserved compared with aged controls (Yau et al 2002). In depressed patients affected by AD and treated with AChEIs, Rozzini et al (2010) found that SSRIs might exert some degree of protection against the negative effects of depression on cognition. The present findings also demonstrated that treatment with donepezil resulted in a decrease of latency time in Morris water maze, thereby suggesting that the AlCl 3 -induced spatial learning deficits are related to cholinergic system impairment by the metal.…”
Section: Discussionmentioning
confidence: 98%
“…A chronic treatment with SSRIs is associated with lower cortical β-amyloid PET signal in cognitively normal elderly human subjects (Cirrito et al, 2011), and with some degree of protection against the negative effects of depression on cognition in AD patients (Rozzini et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Findings also suggest that in treatment of AD patients with cholinesterase inhibitors and SSRIs may offer some degree of protection against the adverse effects of depression on cognition (47). Tricyclic antidepressants are not recommended due to the poor side effects profile.…”
Section: Discussionmentioning
confidence: 99%
“…Reviews indicated that antidepressants (mainly SSRIs) not only showed efficacy in treating BPSD, but were also well tolerated (47,51). Two out of five studies of sertraline versus placebo and one study of sertraline versus haloperidol have shown benefit.…”
Section: Antidepressantsmentioning
confidence: 99%